5+4h=9+2h

Simple and best practice solution for 5+4h=9+2h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+4h=9+2h equation:


Simplifying
5 + 4h = 9 + 2h

Solving
5 + 4h = 9 + 2h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-2h' to each side of the equation.
5 + 4h + -2h = 9 + 2h + -2h

Combine like terms: 4h + -2h = 2h
5 + 2h = 9 + 2h + -2h

Combine like terms: 2h + -2h = 0
5 + 2h = 9 + 0
5 + 2h = 9

Add '-5' to each side of the equation.
5 + -5 + 2h = 9 + -5

Combine like terms: 5 + -5 = 0
0 + 2h = 9 + -5
2h = 9 + -5

Combine like terms: 9 + -5 = 4
2h = 4

Divide each side by '2'.
h = 2

Simplifying
h = 2

See similar equations:

| 0=4x^3+8x^2-28x-56 | | 6xm=1 | | 8(x+3x)=12x+9 | | -2+b-2=10 | | x+80=2x+30 | | 3(2x+5)=14x+8-8x+7 | | -5x-2=26+2x | | (5z-2)=(3z+5) | | (-7.5)+(-4.2)= | | 6.00xm=1 | | 5x+5=5(x+7) | | .12y-.72+.06y=.08y-.7 | | 4*p*4*p= | | -57=27-6x | | -4(x-1)+2=4+6(-x+3) | | (-4x^3y)(5x^2)(-2xy^5)= | | 36h+20=24h+15 | | 25x-7=5(5x+9) | | 8+5x=x+28 | | Y=B^2-6b+8 | | 22-33w-5w=0 | | 27x-13=0 | | 6x+18-3x=24 | | x(a-b)+2=c(x+3)-d | | 5n-10= | | 0.625xa=1 | | -18+4x=-2 | | (3z^5)(4z^5)= | | 5+5=5(x+7) | | 51=3+12x | | (3x^2+2x+1)-(x^2-3x+4)= | | -20+2k=-4k+k |

Equations solver categories